Integration of Sustainable Development Competency Points into the Telecommunication System Subjects at Vocational High School - Agus Heri Setya Budi; Enjang Ahmad Juanda; Dandy Indrawan; H Henny; Masek, Alias (Journal of Technical Education and Training, 2024)
Education for Sustainable Development (ESD) plays a crucial role as an instrumental approach that must be widely promoted to ensure a more advanced and sustainable future. This study aims to comprehensively analyse the successful implementation of ESD in Vocational High Schools (VHS) with a specialisation in the Telecommunication System Subject. To achieve this objective, a research methodology combining document analysis, and interviews was employed. Through document analysis and semi-structured interviews with three subject matter experts among school personnel, pertinent data was gathered. The data encompassed the examination of the syllabus and lesson plans, which were subsequently subjected to meticulous scrutiny using the powerful Maxqda Software. The research findings demonstrate that the existing grading systems and qualification criteria for VHS students align significantly with the core competencies of ESD. However, it is noteworthy that the syllabus and Lesson Plans Study (RPP) themselves lack explicit integration of ESD principles. The effective implementation of Education for Sustainable Development (ESD) heavily relies on the proactive efforts of teachers. Additionally, it is crucial that both the curriculum and lesson plans (RPP) are meticulously revised to integrate key ESD competencies. This approach will help cultivate a generation that is more sustainable, environmentally aware, and socially responsible.